METHODS FOR REDUCING THE ABSORPTION OF ARTIFICIAL BONE MATERIALS USED AFTER NECRECTOMY - Akhrorov Alisher Shavkatovich (Web of Journals Publishing, 2024)
This article investigates various methods to reduce the absorption of artificial bone materials used post-necrectomy, ensuring better integration and long-term stability of bone grafts. Through a detailed analysis of existing literature and experimental studies, we explore techniques such as surface modifications, the use of bioactive coatings, and the incorporation of osteoinductive factors to enhance the durability of artificial bone substitutes. The study aims to provide practical solutions for improving the clinical outcomes of bone repair surgeries.
Keywords: Artificial bone, necrectomy, bone absorption, bioactive coating, surface modification, osteoinduction, bone repair.